2001
DOI: 10.1128/aem.67.7.3325-3327.2001
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Klebsiella Species in Surface Waters and Their Expression of Virulence Factors

Abstract: To investigate the occurrence of different Klebsiella spp. in aquatic environments, a total of 208 samples of natural surface waters was examined. From half (53%) of these samples, 123 Klebsiella strains were isolated, the most common species being Klebsiella pneumoniae. A comparison of these isolates to a group of 207 clinical K. pneumoniae isolates demonstrated that water isolates of K. pneumoniae, unlike those of K. oxytoca and K. planticola, are as capable as clinical isolates of expressing putative virule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
124
0
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(134 citation statements)
references
References 23 publications
5
124
0
5
Order By: Relevance
“…The environment can contain a large variety of K. pneumoniae strains with pathogenic potential (26,30), and mastitis cases within a dairy herd are usually caused by many different strains (3,(23)(24)(25). Predominance of a single K. pneumoniae strain, such as RAPD type A in the first outbreak of CM described here, is unusual.…”
Section: Discussionmentioning
confidence: 99%
“…The environment can contain a large variety of K. pneumoniae strains with pathogenic potential (26,30), and mastitis cases within a dairy herd are usually caused by many different strains (3,(23)(24)(25). Predominance of a single K. pneumoniae strain, such as RAPD type A in the first outbreak of CM described here, is unusual.…”
Section: Discussionmentioning
confidence: 99%
“…The accurate identification of K. pneumoniae strains is increasingly necessary, not only because the systematics of Klebsiella has changed (Brisse et al 2014;Martínez et al 2004), but also because these strains differ in their virulence and antibiotic susceptibility (Podschun et al 2001). Accurate and rapid identification can facilitate the successful early resolution of infections and the subsequent reduction of morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Klebsiella was highest in the Mooi and Vaal followed by Harts catchments with 19% and 11%, respectively. Podschun et al (2001) also reported a high percentage (53%) distribution of Klebsiella spp. from surface water samples, the most common species being K. pneumoniae.…”
Section: Resultsmentioning
confidence: 99%